Beck Depression Inventory-II: Self-report or interview-based administrations show different results in older persons - Stepankova Georgi, Hana; Horakova Vlckova, Karolina; Lukavsky, Jiri; Kopecek, Miloslav; Bares, Martin (International psychogeriatrics, 2019)
UNLABELLED: ABSTRACTBeck Depression Inventory-II (BDI-II) is one of the most-used rating scales. It was developed as a tool administered either as a self-rating or interview-based, observer-rating scale. OBJECTIVE: The goal of this study is to compare BDI-II scores obtained with two standard methods of administration in community-based older persons. METHODS: BDI-II was administered at first in the self-rated version to a sample of 60 mentally healthy older persons (age 60-87 years). Afterward, the interview-based administration was performed. ANALYSES: We compared the scores with nonparametric tests - Spearman's correlation coefficient and Wilcoxon Signed Ranks test. We also computed internal consistency. RESULTS: Self-rated BDI-II yielded significantly higher total score than interview (p < 0.001, P = 88%). The correlation between total scores was moderate (rs = 0.46, p < 0.001). Item analysis revealed a larger decrease (lower scores) in the somatic items in the interview-based version. CONCLUSIONS: The two methods of administration result in different total score in healthy older persons. Therefore, interpretation of the scores should reflect the administration, which should be always specified in the studies.
Keywords: rating scales; senioři; Psychometrics; Reproducibility of Results; deprese; senioři nad 80 let; Beck Depression Inventory; psychometrie; depression; research design and methodology; reprodukovatelnost výsledků; zpráva o sobě; Depression; Middle Aged; mužské pohlaví; depresivní poruchy; Self Report; Aged, 80 and over; ženské pohlaví; Humans; lidé středního věku; interview psychologický; psychogeriatrics; Female; Aged; Interview, Psychological; Depressive Disorder; lidé; Male